2021
DOI: 10.1002/ccd.29489
|View full text |Cite
|
Sign up to set email alerts
|

Heartech® left ventricular partitioning device improves left ventricular systolic function of patients with chronic heart failure post‐myocardial infarction at 1‐year follow‐up

Abstract: Objectives: This study presents 1-year follow-up data of echocardiographic outcomes in patients who received the Heartech ® left ventricular (LV) partitioning device (LVPD) (Xinrui Medical Equipment Co. Ltd., Shanghai, China).Background: Our first-in-man study of the Heartech ® LVPD confirmed its safety and efficacy in patients with chronic heart failure (HF) post-myocardial infarction (MI) 1 month post-implantation. This subsequent study reports the echocardiographic outcomes of these patients at 1 year of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this current issue of Catheterization and Cardiovascular Interventions, Su et al reported the 1-year follow-up of 15 patients with heart failure after anterior STEMI, who received the Heartech LV partitioning device. 5 This device is produced in China "with a similar design as that of the Parachute." Of the 16 patients enrolled, one was excluded due to failed device placement and one patient died of progressive heart failure.…”
mentioning
confidence: 99%
“…In this current issue of Catheterization and Cardiovascular Interventions, Su et al reported the 1-year follow-up of 15 patients with heart failure after anterior STEMI, who received the Heartech LV partitioning device. 5 This device is produced in China "with a similar design as that of the Parachute." Of the 16 patients enrolled, one was excluded due to failed device placement and one patient died of progressive heart failure.…”
mentioning
confidence: 99%